2021
DOI: 10.1038/s41467-020-20283-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional THz emitters based on Pancharatnam-Berry phase nonlinear metasurfaces

Abstract: Recent advances in the science and technology of THz waves show promise for a wide variety of important applications in material inspection, imaging, and biomedical science amongst others. However, this promise is impeded by the lack of sufficiently functional THz emitters. Here, we introduce broadband THz emitters based on Pancharatnam-Berry phase nonlinear metasurfaces, which exhibit unique optical functionalities. Using these new emitters, we experimentally demonstrate tunable linear polarization of broadba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
105
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(111 citation statements)
references
References 39 publications
1
105
0
Order By: Relevance
“…Gennaro et al [193] demonstrated nonlinear diffraction of FWM, finding corrections to the dipole approximation of the PB phase for composite meta-atoms [Fig. 14(f [194] demonstrated spatial and temporal shaping of THz waves generated via DFG (second order optical rectification), using functional nonlinear PB metasurfaces [Fig. 14(g)].…”
Section: Nonlinear Pancharatnam-berry Beam Steering Beam Shaping and Holographymentioning
confidence: 99%
See 3 more Smart Citations
“…Gennaro et al [193] demonstrated nonlinear diffraction of FWM, finding corrections to the dipole approximation of the PB phase for composite meta-atoms [Fig. 14(f [194] demonstrated spatial and temporal shaping of THz waves generated via DFG (second order optical rectification), using functional nonlinear PB metasurfaces [Fig. 14(g)].…”
Section: Nonlinear Pancharatnam-berry Beam Steering Beam Shaping and Holographymentioning
confidence: 99%
“…14(g)]. Interestingly, for FWM and DFG, more intricate selection rules arise [193,194], that are based on the symmetry of the meta-atoms and conservation of spin-angular momentum [176]. In this context, the authors of Ref.…”
Section: Nonlinear Pancharatnam-berry Beam Steering Beam Shaping and Holographymentioning
confidence: 99%
See 2 more Smart Citations
“…Terahertz (THz) waves located at the special frequency range of 0.1–10 THz on electromagnetic wave spectrum possess various excellent properties, visualizing the formation of the basis for future intelligent perception and imaging, [ 1–3 ] the next‐generation high‐speed wireless communications, [ 4–7 ] and so on. Rapid progresses on developing high‐energy THz sources, [ 8,9 ] ultrasensitive detectors, [ 10–13 ] and various functional devices [ 14–19 ] enable THz technologies to walk out from laboratories to serve significant strategic needs possible. Among numerous important demands, THz radars and communication [ 4–7 ] are one of most likely to be wide‐spread applied soon.…”
Section: Introductionmentioning
confidence: 99%